Targeting of early endosomes by autophagy facilitates EGFR recycling and signalling. (26th August 2019) - Fraser, Jane; Simpson, Joanne; Fontana, Rosa; Kishi‐Itakura, Chieko; Ktistakis, Nicholas T; Gammoh, Noor
Abstract: Despite recently uncovered connections between autophagy and the endocytic pathway, the role of autophagy in regulating endosomal function remains incompletely understood. Here, we find that the ablation of autophagy‐essential players disrupts EGF‐induced endocytic trafficking of EGFR. Cells lacking ATG7 or ATG16L1 exhibit increased levels of phosphatidylinositol‐3‐phosphate (PI(3)P), a key determinant of early endosome maturation. Increased PI(3)P levels are associated with an accumulation of EEA1‐positive endosomes where EGFR trafficking is stalled. Aberrant early endosomes are recognised by the autophagy machinery in a TBK1‐ and Gal8‐dependent manner and are delivered to LAMP2‐positive lysosomes. Preventing this homeostatic regulation of early endosomes by autophagy reduces EGFR recycling to the plasma membrane and compromises downstream signalling and cell survival. Our findings uncover a novel role for the autophagy machinery in maintaining early endosome function and growth factor sensing. Synopsis: Targeting of damaged organelles by autophagy is crucial for cell homeostasis. This study identifies a novel function of the autophagy machinery in recognising damaged early endosomes, the absence of which compromises EGFR trafficking and signalling. Aberrant early endosomes accumulate in the absence of autophagy. Lysosomes are recruited to damaged early endosomes requiring the activities of TBK1, Gal8, and the autophagy machinery. The consequence of unresolved early endosome damage is the disruption of EGFR trafficking and compromised EGF‐mediated signalling and survival. Abstract : Targeting of damaged organelles by autophagy is crucial for cell homeostasis. This study identifies a novel function of the autophagy machinery in recognising damaged early endosomes, the absence of which compromises EGFR trafficking and signalling.